Microbial Transformations of Aryltetralone and Aryltetralin Lignans by Cunninghamella echinulata and Beauveria bassiana - Messiano, Gisele B. [UNESP]; Wijeratne, E. M. Kithsiri; Lopes, Lucia Maria Xavier [UNESP]; Gunatilaka, A. A. Leslie (Amer Chemical Soc, 2010)
Microbiological transformation of the aryltetralone lignan (-)-8'-epi-aristoligone (1) with Cunninghamella echinulata ATCC 10028B afforded two known natural lignans, (-)-holostyligone (3) and (-)-arisantetralone (4). Incubation of the aryltetralin lignan (-)-isogalbulin (2), obtained by chemical transformation of 1, with C. echinulata ATCC 10028B afforded the known lignan aryltetralol (5) and seven new metabolites, (-)-8-hydroxylsogalbulin (6), (-)-7-methoxyisogalbulin (7), (-)-4'-O-demethyl-8-hydroxyisogalbulin (8), (-)-7-methoxy-8-hydroxyisogalbulin (9), (-)4'-O-demethyl-7-methoxyisogalbulin (10), (-)-4',5-O-didemethylcyclogalgravin (11), and (-)-4'-O-demethylcyclogal-gravin (12). When 2 was subjected to biotransformation with Beauveria bassiana ATCC 7159, (-)-8-hydroxyisogalbulin (6) was the only isolable product. The structures of all new compounds were established by detailed analysis of their spectroscopic data.